PENERAPAN KURIKULUM MERDEKA DALAM UPAYA MENGATASI LEARNING LOSS MENUJU PENDIDIKAN YANG BERKOMPETENSI UNGGUL - Usamah, Tin Nur (Jurusan Pendidikan Bahasa, Fakultas Ilmu Budaya, Universita Brawijaya, 2022)
Abstract The purpose of this research is limited face-to-face learning (PTMT) to optimize activities and learning outcomes at SMA Panjura Malang and can overcome learning loss or decrease learning achievement, and can create superior competencies and independent learning. Applications carried out in limited Face-to-face Learning (PTMT) at SMA Panjura Malang: Strategies and Efforts to Approach Students' Psychological, or Mental Readiness (Diagnostic Analysis) before conducting PTMT, Habits Strategy to introduce school environment or school habitat (scholl habitat) with restoration of education to PTMT, Strategy for Providing complete facilities and infrastructure for PTM Implementation, PTMT Implementation Process Strategy in Learning, Covid-19 Prevention and Control Strategy, Covid Alert Bag Strategy, Strategies and Efforts to Possess PTS and PAS exams, Strategy for Reporting PTMT learning outcomes periodically with report cards Monthly, Friendly and Disciplined Environmental Culture Strategy, Well-being, Learning Strategy with Hybrid Learning. Keywords: learning loss, PTMT strategy, superior competence